The siren song of vocal fundamental frequency for romantic relationships - Weusthoff, Sarah; Baucom, Brian R.; Hahlweg, Kurt (Frontiers in Psychology, 2013)
A multitude of factors contribute to why and how romantic relationships are formed as well as whether they ultimately succeed or fail. Drawing on evolutionary models of attraction and speech production as well as integrative models of relationship functioning, this review argues that paralinguistic cues (more specifically the fundamental frequency of the voice) that are initially a strong source of attraction also increase couples’ risk for relationship failure. Conceptual similarities and differences between the multiple operationalizations and interpretations of vocal fundamental frequency are discussed and guidelines are presented for understanding both convergent and non-convergent findings. Implications for clinical practice and future research are discussed.